DISKURSUS PARADIGMA MAKROEKONOMI INKLUSIF DALAM PERSPEKTIF AL-QUR’AN: TINJAUAN TAFSIR KONTEKSTUAL PADA AYAT-AYAT MATA UANG DALAM PARADIGMA ORTODOKS DAN HETERODOKS - Unggul Purnomo Aji; Kerwanto; Nurbaiti (LP2M Universitas PTIQ Jakarta, 2025)
This study discusses the dichotomy of economic paradigms, examined both theoretically and practically, in relation to the value of economic inclusivity, and aims to contextualize the definitions of monetary verses in the Qur’an. The research was undertaken because the interpretation of currency by the majority of mufassir (Qur’anic commentators), Islamic academics, and economists has misinterpreted the meaning of money when linked to the development of today’s monetary system. This study employs a literature review method and thematic interpretation that is appropriate given the relevance of non-field data samples. The findings indicate that the heterodox economic paradigm is more coherent than the orthodox paradigm from a theoretical standpoint, and this view is supported by strong archaeological evidence. A monetarily sovereign government is at least capable of purchasing anything domestically, including employing the entire unemployed population. In addressing poverty, inequality, unemployment, and inclusivity, the heterodox paradigm features a consumption-led growth program that is considerably more efficient and has a better economic impact compared to the orthodox paradigm’s investment-led growth policy proposals. In terms of interpretation, the understanding of money as a medium of exchange from the orthodox paradigm is only suitable for mercantile societies without authority, as was the case in the Arab world during the Jahiliyyah era, whereas the definition of money as a unit of account is a more appropriate definition to be used today in light of the differences and advancements in the monetary system